Hospital Closure and Insights into Patient Dispersion - Garg, N.; Husk, G.; Nguyen, T.; Onyile, A.; Echezona, S.; Kuperman, G.; Shapiro, J.S. (Applied Clinical Informatics, 2015)
Background: Hospital closures are becoming increasingly common in the United States. Patients who received care at the closing hospitals must travel to different, often farther hospitals for care, and nearby remaining hospitals may have difficulty coping with a sudden influx of patients.Objectives: Our objectives are to analyze the dispersion patterns of patients from a closing hospital and to correlate that with distance from the closing hospital for three specific visit types: emergency, inpatient, and ambulatory.Methods: In this study, we used data from a health information exchange to track patients from Saint Vincent’s Medical Center, a hospital in New York City that closed in 2010, to determine where they received emergency, inpatient, and ambulatory care following the closure.Results: We found that patients went to the next nearest hospital for their emergency and inpatient care, but ambulatory encounters did not correlate with distance.Discussion: It is likely that patients followed their ambulatory providers as they transitioned to another hospital system. Additional work should be done to determine predictors of impact on nearby hospitals when another hospital in the community closes in order to better prepare for patient dispersion.Citation: Garg N, Husk G, Nguyen T, Onyile A, Echezona S, Kuperman G, Shapiro JS. Hospital closure and insights into patient dispersion: the closure of Saint Vincent’s Catholic Medical Center in New York City. Appl Clin Inf 2015; 6: 185–199http://dx.doi.org/10.4338/ACI-2014-10-RA-0090
Keywords: Health information systems; health services research; health facility closure; medical informatics; health policy